2001
DOI: 10.1086/318796
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Perforin Gene Mutations in Familial Hemophagocytic Lymphohistiocytosis

Abstract: Familial hemophagocytic lymphohistiocytosis (FHL) is an autosomal recessive disease of early childhood characterized by nonmalignant accumulation and multivisceral infiltration of activated T lymphocytes and histiocytes (macrophages). Cytotoxic T and natural killer (NK) cell activity is markedly reduced or absent in these patients, and mutations in a lytic granule constituent, perforin, were recently identified in a number of FHL individuals. Here, we report a comprehensive survey of 34 additional patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(146 citation statements)
references
References 35 publications
10
135
1
Order By: Relevance
“…47,48 Patients with FHL usually present in infancy or very early in childhood and in the absence of bone marrow transplantation most patients die within 1 year after diagnosis. 23,27,49 Patients with FHL and nonsense mutations tend to present within the first few months of life, whereas those with missense mutations usually present by 2 years of age. 23 Although our patient showed many of the features of FHL early in the course of his disease, 22 he presented at an older age (7 years) than most patients with FHL, survived for 10 years after diagnosis, and did not have a family history of hemophagocytic lymphohistiocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Patients with FHL usually present in infancy or very early in childhood and in the absence of bone marrow transplantation most patients die within 1 year after diagnosis. 23,27,49 Patients with FHL and nonsense mutations tend to present within the first few months of life, whereas those with missense mutations usually present by 2 years of age. 23 Although our patient showed many of the features of FHL early in the course of his disease, 22 he presented at an older age (7 years) than most patients with FHL, survived for 10 years after diagnosis, and did not have a family history of hemophagocytic lymphohistiocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the identification of this gene, which is responsible for the disease in a subgroup of patients, 2 several groups have reported on the identification of novel mutations. [3][4][5][6] Small deletions and nonsense and missense mutations were described and scattered both coding exons of the gene. In this family, the homozygous A91V and the heterozygous R231H exchange was detectable in both twins, one of them presenting typical signs of hemophagocytic lymphohistiocytosis (HLH) at the age of 11 years with a rapidly fatal course of the disease.…”
Section: A91v Is a Polymorphism In The Perforin Gene Not Causative Ofmentioning
confidence: 99%
“…[1][2][3][4][5][6] Flow cytometric detection of perforin in peripheral blood natural killer (NK) cells and cytotoxic T lymphocytes was previously studied in a small number of patients by our group and suggested that flow cytometry offered a rapid and sensitive approach for detection of perforin deficiency. 7 To more accurately determine the clinical diagnostic accuracy of flow cytometric screening for the detection of PRF1 mutations, we reviewed the reported results of 750 clinical samples submitted to the Diagnostic Immunology Laboratory at Cincinnati Children's Hospital by the ordering physician for perforin testing between August 2009 and December 2014; genetic sequencing was also performed as directed by the ordering physician.…”
mentioning
confidence: 99%